Prototipe Aplikasi Hepatitis BC Maps Meningkatkan Pengetahuan Pendonor Sukarela di UDD PMI Kota Kediri Tentang Hepatitis B dan C - Fandina, Titania Auril; Ariani, Nia Lukita; Hupitoyo, Hupitoyo (Care : Jurnal Ilmiah Ilmu Kesehatan, 2023)
The prevalence of Hepatitis B and C remains high in Indonesia. These diseases impact health, productivity, social interactions, and financial status. Applying digital technology to prevent the spread of hepatitis B and C using the Hepatitis BC Maps application is an important innovation. The objective of this study was to compare people's knowledge of hepatitis B and C before and after receiving education via the Hepatitis BC Maps application prototype at the PMI Kediri. The research design was quasi-experimental with a time-series design for a single group. To obtain a sample of 66 people, a simple random sampling technique was used to determine the research sample. This study employed univariate descriptive analysis and the Wilcoxon signed-rank test for data analysis. Pretest and posttest questionnaires were utilized for data collection. After receiving an education using the Hepatitis BC Maps application prototype, the level of knowledge of voluntary blood donors at the PMI Kediri increased. Numerous variables, including education, information, occupation, and age influence the knowledge level. This educational feature is a visual medium that can aid in memory retention because it allows one to visualize something that is explained more concretely and realistically.